Management of ovarian granulosa cell tumor in childhood: a case report and recommendations for a multidisciplinary approach - Arnaboldi, Sofia Maria Carlotta; Gattuso, Giovanna; Nicolosi, Maria Laura; Molinari, Silvia; Bettini, Laura Rachele; Leva, Ernesto; Passoni, Paolo; Chiappa, Valentina; Daolio, Cecilia; Balduzzi, Adriana Cristina; Massimino, Maura; Terenziani, Monica; et al. (Frontiers in Oncology, 2025)
Juvenile granulosa cell tumor (jGCT) is a rare subtype of pure sex-cord tumors, mostly affecting patients under 20 years of age. As this tumor originates from ovarian cells specialized in sex steroid secretion, jGCT can present with endocrine disorders, including precocious puberty in prepubertal girls or menstrual irregularities in postpubertal patients. In other cases, jGCT may manifest with symptoms related to pelvic mass effects or acute abdomen, prompting urgent gynecologic or surgical evaluation. Most patients are diagnosed with ovarian-confined disease, and for these patients, the survival rates exceed 90% following surgery alone. However, advanced and relapsed disease remains a significant concern. As the survival rates for cancer continue to improve, addressing survivorship care is essential. Long-term follow-up for patients diagnosed with jGCT in childhood requires a multidisciplinary approach. We hereby describe a clinical case of jGCT diagnosed in an infant girl for whom a comprehensive multidisciplinary care plan was arranged. Through a comprehensive review of the literature, we developed a clinically applicable flowchart for the multidisciplinary management of jGCT at diagnosis and during follow-up, emphasizing the need for patient-centered care that integrates the work of oncologists, endocrinologists, surgeons, gynecologists, and geneticists.